F(-2) = 4x(-2) = -8;
g(f(-1))= g(-8) = 2x(-8) -1 = -16 - 1 = -17.
Answer:
5
Step-by-step explanation:
<u>Steps of calculation:</u>
- 7 + 1 - 18 : 6 =
- 7 + 1 - 3 =
- 8 - 3 =
- 5
Answer is 5
Answer:
Step-by-step explanation:
To factor,
<h2>
[[[</h2>
1) First multiply coefficient of a² and constant no,
That is,
3×(-42)=-126
Since the<u> resultant no is negative</u>, you should find two such factors of 126 <u>which</u> <u>will give us the coefficient of a (=11)</u> on subracting those factors.
2) Find the factor
126=2×3×3×7
=18×7
18 and 17 are factors of 126
Also,18-7 =11.
So they are required factors for factoring,
<h2>
]]]</h2>
Once you have understood above steps you can solve on your own. All you need to do is split 11 into factors ,take common terms and you will get answer.
<u>Answer:</u>
3a²+11a-42
=3a²+(18-7)a -42
=3a²+18a-7a-42
=3a(a+6) -7(a+6)
=(a+6)(3a-7)